Covid-19 pandemic and its impact on increasing the risks of children's addiction to electronic games from a social work perspective. Issue 12 (December 2021) - Elsayed, Walaa
Abstract: Children are among the social groups most affected by the COVID-19 pandemic because they have found themselves forced to stay at home, far from their schoolmates, their friends, and far from all the activities they used to do before the pandemic. so, it was their only refuge for recreation during their stay in Home is staying in front of the screens of tablets, smartphones, and computers to play electronic games for long hours, and there is no doubt that the sudden shift in the lifestyle of children during the Covid-19 pandemic had serious consequences and risks threatening their stability at all levels. In light of that, the current study aimed to determine the impact of the Covid-19 pandemic on increasing the social, psychological, behavioral, and health risks of children's addiction to electronic games from a social work perspective. This study falls under the type of descriptive-analytical studies that are based on describing the reality of the problem under study. The study sample included 289 children in the age group 6–17 years in the first grade to the twelfth grade at school. The researcher designed a questionnaire that reflects the four risks facing children to assess these risks. The results showed is that the value of all impacts of the Covid-19 pandemic on the increasing risks of children's addiction to electronic games came to a total weight of (27907), weighted relative weight of (80.47%). This indication is High, indicating that the level of impact is High for the Covid-19 pandemic on the increase in all types of risks of children's addiction to electronic games. It ranked first " Behavioral Risks " at 91.15%, It is followed by the ranked second "Social risks " at 85.5%, Then came third place " Psychological Risks" at 80.91%, and in finally in fourth place " Health Risks" at 64.28%, which necessitates the need to take a set of serious measures by educating parents to monitor the content of electronic games that their children play, especially violent games, in addition to, reduce the number of hours the child spends practicing these games, and to encourage parents to form a bridge of communication and constructive dialogue between them and their children, and that parents put controls and restrictions on their children's practice of electronic games to confront abnormal behavioral, psychological and social patterns such as aggression, violence, deception, lying, imitation, vigilance, physical stress, poor eyesight, distance from practicing religious rituals, academic delay, introversion, depression, intolerance, selfishness, sadness, isolation from society, social withdrawal and lack of forming social relationships and lack of communication with others. The researcher took care that the results of the current study are very accurate and representative of the reality of the research problem, in light of the researcher's emphasis on the commitment to observe ethical rules to ensure the confidentiality of data. finally, the current study will greatly benefit researchers interested in the field of childhood and its problems and they will rely on its results and recommendations in how to protect children from the dangers of electronic game addiction in light of the Covid-19 crisis in particular. Abstract : Electronic games; Addiction; Risks; Children; Social work.